A Feasible Enzyme-Linked Immunosorbent Assay System Using Monoclonal and Polyclonal Antibodies Against Glucosyltransferase-B from Streptococcus mutans - Shinozaki-Kuwahara, Noriko (Mary Ann Liebert, Inc., 2012)
STREPTOCOCCUS MUTANS: has been considered the principal etiological agent of dental caries in humans. S. mutans can secrete three kinds of glucosyltransferases (GTFs). One of these, GTF-B, which synthesizes water-insoluble glucans from sucrose, has been considered to be one of the most important factors of cariogenic dental plaque formation. Therefore, determination of whether GTF-B is present in plaque and saliva samples may contribute to the evaluation of individual virulence potential (caries risk). The aim of this study was to develop a feasible enzyme-linked immunosorbent assay (ELISA) for the routine quantification of GTF-B in plaque-derived cultures and clinical samples, and to apply this assay to an epidemiological study. To determine the presence of GTF-B in plaque samples, a sandwich-ELISA was devised, consisting of mouse monoclonal and rabbit polyclonal antibodies against GTF-B and a horseradish peroxidase-conjugated anti-rabbit antibody. The developed ELISA allowed for quantification of the amounts of purified GTF-B with satisfactory sensitivity and specificity; this method was not affected by other components such as plaque and saliva. Plaque samples from healthy volunteers were examined using this ELISA method and microbial analysis to apply the assay to an epidemiological study. A correlation was observed between the amount of extracted GTF-B and S. mutans levels as determined by ELISA and cultivated with Mitis Salivarius Bacitracin agar plates derived from plaque samples, although there were some exceptions. In this regard, this ELISA system has the advantage of estimating both the individual numbers of S. mutans and the productivity of GTF-B, namely, the cariogenic potential of S. mutans simultaneously. These results indicate that this ELISA method is a useful tool for the diagnosis of caries risk.